Corporate social responsibility disclosure to firm value with family ownership as moderating variable / Gusrianti … [et al.] - ., Gusrianti; Nirmala, Muthia Prima; Kamela, Hurian; D. Djakman, Chaerul; Adhariani, Desi (Faculty of Accountancy, 2019)
The growing concern on social and environmental issues from various stakeholders create the demand for CSR disclosures, however the impact on firm value is mixed. This study aims to obtain empirical evidence on the association of corporate social responsibility (CSR) disclosure and firm value with family ownership as the moderating variable. We argue that family firms will strengthen the association as family owners will try to keep the good reputation of their company and maintain good relationships with stakeholders. Quantitative method is used to investigate this issue by performing moderated regression on a sample of manufacturing companies in Indonesia. The number of samples is 196 firm-year observation for the research period of 2014-2016 selected using purposive sampling technique. The results show that CSR disclosure had a positive effect on firm value, but there was no role of moderation of family ownership variables found on the association. The insignificant role is likely due to the effect of weak control from pyramid-shaped ownership on firms in Indonesia. The contribution of this research is expected to provide an overview of CSR disclosure and its relation to firm value in the context of family companies in Indonesia.